Minat Belajar Musik Instant Akibat Respon Berulang Dan Menyenangkan Pada Ajang Pentas Kompetisi Musik Populer; “Studi Kasus Pendidikan Musik Nonformal dalam Sudut Pandang Teori Belajar Operant Conditioning BF. Skinner” - Esy Maestro; Mudjiran Mudjiran (FBS Universitas Negeri Padang, 2021)
Thedevelopment of music in modern and urban society today is not always driven by the awareness of the importance of formal education in the field of music itself. The behavior of the community that develops in the surrounding environment, psychologically has triggered the interest of some individuals to engage in the phenomenon of populist music culture, one of which is budaya K-pop who participated in fertilizing music talent search competitions such astelevision, initiated bylocalgovernments, and certain nongovernmental organizations. Many parents consider that their children need to take part either as serious participants or just perform in the event. Many young people and their parents are willingto spendmoney, time, energy, and cost in order to be exposed to the event that is considered prestigious. The continuation is predictable, while the prizes are obtained,of coursepopularity follows, because they will be widely published by the services of the media and television. A number of thesefinancial r ewards and popularity will be enjoyable. The behavior to repeat and keep repeating the participation ofchildren in this event , aslong asitcauses them to havebeen trapped in the behavior of operant conditioning. So BF. Skinner has explained that if a stimulus produces a pleasant reward support capacity,there will be consequences for repeated behavioral responses. Because it will repeat itself, some young people are trying to develop their musical interests by learning music from an early age or studying it in formal education. But the irony for some of them is that it synergizes with the impatience of their parents, to learn music in more results-oriented and instantaneous music courses. The managers of this kind of non-formal music education institutions seem to also care about the quality of music education, unless they also feel equally profiting momentarily from this phenomenon. Eventually many participants of the courseand tutors were disappointed at the incompatibility of the results obtained with all the power that had been sacrificed. In fact, it is still the really talented children who continue to advance to win this talent search competition, even though there are actually some of these champions who learn or do not need to study in courses and less private music.